Clinical Significance of Anatomical Variations in Renal Vasculature among Pakistani Population with Normal Renal Functions - Misbah Ishtiaq, Fazal-Ur-Rehman Khan, Muhammad Hamza Azhar, Shaheer Azhar, Anwar-Ul-Haq, Mian Azhar Ahmad (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Anatomical variations in renal vasculature provide optimal patient care and minimize the complications during surgical procedures and interventional radiology. Objective: To assess the clinical significance of anatomical variations in renal vasculature among Pakistani population with normal renal functions. Study design: Cross-sectional analytical study Place and duration of study: Shaikh Zayed Hospital, Lahore from 15th March 2021 to 14th March 2023. Methodology: One hundred and fifty cases were examined belonging to both gender within the age group of 18 to 65 years which were advised renal imaging as per protocol for evaluating potential donor for renal transplant surgery or any other reason for which renal CT angiography scan was performed. The protocol for renal scan included patients to be empty stomach for at least 6 hours. In patients where more than one artery was identified the vessel with maximum diameters was taken as the renal artery with other classifies as accessory arteries. Within the accessory artery further division were made as superior or inferior polar/hilar group depending upon their site as polar or hilum. Early pre-hilar branching was termed as branching from main renal-artery as 1.5 cm far from hilum. Results: The mean age of the patients was between 55.6±2.2 years with 56.6% males and 43.4% females. There was obvious variation observed in the diameter of renal arteries within male and female cases. The frequency of accessory artery within genders presented highest number of cases of males with accessory renal artery. The percentage of left renal artery was 7% in males and 4% in females. The association of laterality with accessory renal artery presented highest number of superior polar branching in accessory renal artery followed by inferior polar artery in females. There was no superior polar or inferior polar branching was observed in the right renal artery. Majority of the male cases presented with single renal artery with prehilar branching being presented In 45.18% cases. The dual renal artery was also presented in few cases. Conclusion: The variation of renal vascularity with existence of accessory renal arteries. The pre-hilar branching was presented highest and was associated with left renal artery in it the knowledge of such variation before renal surgery is important to get the best results Keywords: Significance, Anatomical variation, Renal vasculature, Renal function